The effect of competition and industrial concentration on banking stability: The case of Vietnam - Dang, Thuy T; Lan, Le Thi; Linh, Nguyen Tran Xuan; Nguyen, Hau Trung (Journal of Social Economics Research, 2025)
This study examines the impact of industry concentration and competition on the stability of the Vietnamese banking system, which has undergone significant restructuring in recent years. Using Bayesian regression analysis on data from 27 commercial banks between 2011 and 2021, the study measures banking stability through the Z-score and the ratio of non-performing loans (NPLs), while industry concentration and competition are assessed via the Herfindahl-Hirschman Index (HHI) and the Lerner Index, respectively. The findings reveal that industry concentration has a limited effect on banking stability, whereas competition plays a crucial role in strengthening financial resilience. Banks with higher market power, as reflected by the Lerner Index, exhibit greater stability, with a 100% probability of improving financial soundness. Additionally, a higher equity-to-assets ratio significantly enhances bank stability by reducing financial risk, while income diversification helps lower NPL ratios. The study also finds that macroeconomic factors such as credit growth, inflation, and the COVID-19 pandemic have mixed effects on banking stability. These findings emphasize the need for policymakers to prioritize enhancing banking competitiveness rather than solely focusing on industry concentration. Regulatory measures should promote non-interest income activities, facilitate digital banking development, and strengthen capital adequacy in line with Basel II and Basel III standards. Ensuring financial resilience through strategic consolidation and effective risk management is essential for the long-term stability and sustainable development of Vietnam’s banking sector.